Fund governance and flow performance relationship. Issue 1 (2nd January 2023) - Khan, Saleh Nawaz; Noor, Amna
ABSTRACT: The mutual fund flow–performance relationship remains the interest of academic researchers all the time. It is widely accepted that the flow performance relationship curve is convex in nature. Unfortunately, we have very limited knowledge about the sources behind this convexity. This study posits a new variable, fund governance, that impacts the convexity of the flow performance relationship. The estimation technique applied in this study is the least square regression model with white robust standard error and covariance matrix. The results exhibit that the convexity in the flow performance relationship is positively related to good fund governance practices.